Stability of triangular equilibrium points in the Photogravitational elliptic restricted three body problem with Poynting-Robertson drag - Mishra, Vivek; Sharma, J.P.; Ishwar, Bhola (International Journal of Advanced Astronomy, 2016)
We have examined the stability of triangular equilibrium points in photogravitational elliptic restricted three-body problem with Poynting-Robertson drag. We suppose that smaller primary is an oblate spheroid. We have taken bigger primary as radiating. We have found the location of triangular equilibrium points and characteristic equation of the problem. We conclude that triangular equilibrium points remain unstable, different from classical case.